2013
DOI: 10.1039/c3ob40703a
|View full text |Cite
|
Sign up to set email alerts
|

Tunable electronic interactions between anions and perylenediimide

Abstract: Over the past decade anion-π interaction has emerged as a new paradigm of supramolecular chemistry of anions. Taking advantage of the electronic nature of anion-π interaction, we have expanded its boundaries to charge-transfer (CT) and formal electron transfer (ET) events by adjusting the electron-donating and accepting abilities of anions and π-acids, respectively. To establish that ET, CT, and anion-π interactions could take place between different anions and π-acids as long as their electronic and structura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 64 publications
6
60
0
Order By: Relevance
“…Saha and coworkers showed that addition of strongly Lewis basic anions to electron-deficient naphthalene diimides (NPI) leads to anion–π interactions that ultimately result in reduction and generation of the corresponding [NPI]˙ – radical anions. 18 It seems plausible then that in the case of BDT-PT and BDT-2PT , where anion binding to boron is sterically hindered by the very bulky substituent, reduction of the compounds by F – effectively competes with the anion binding to boron. This process would be less favorable when using [Bu 4 N][Ph 3 SiF 2 ] as the F – source due to the diminished reducing power of the fluorosilicate complex.…”
Section: Resultsmentioning
confidence: 99%
“…Saha and coworkers showed that addition of strongly Lewis basic anions to electron-deficient naphthalene diimides (NPI) leads to anion–π interactions that ultimately result in reduction and generation of the corresponding [NPI]˙ – radical anions. 18 It seems plausible then that in the case of BDT-PT and BDT-2PT , where anion binding to boron is sterically hindered by the very bulky substituent, reduction of the compounds by F – effectively competes with the anion binding to boron. This process would be less favorable when using [Bu 4 N][Ph 3 SiF 2 ] as the F – source due to the diminished reducing power of the fluorosilicate complex.…”
Section: Resultsmentioning
confidence: 99%
“…On photoirradiation by unfiltered white light of ax enon lamp in the presenceo fT EOA, the absorption bandso fPBI-9-An at 512 nm decreased, and new absorptionb ands centered at 708, 802, 864, and 954 nm appeared and intensified, which are the characteristicD 0 !D n absorption of PBIC À À . [91][92][93] Notably, the absorption band centered at 369 nm (AN absorption) do not change, that is, the AN moiety remains intact during photoreduction. This implies that PBIC À À is formed,d ue to photoreductionofthe dyad in the presence of TEOA.…”
Section: Dft Calculationsmentioning
confidence: 99%
“…In the presence of BPPN‐2OH , the signal for the F − anions shifted upfield from −113 to −127 ppm (Figure S10), consistent with shielding of F − ions by the PBI core and the biphenyl group. In addition, a broad singlet appeared at −153 ppm, representing HF 2 − anions . In the 19 F NMR spectra, the lack of any other new signals for F − species ruled out the possibility of covalent C−F bond formation through nucleophilic attack of an F − anion on the PBI core.…”
Section: Resultsmentioning
confidence: 98%